2018
DOI: 10.1016/s2352-3026(18)30053-x
|View full text |Cite
|
Sign up to set email alerts
|

Automated typing of red blood cell and platelet antigens: a whole-genome sequencing study

Abstract: National Human Genome Research Institute, Doris Duke Charitable Foundation, National Health Service Blood and Transplant, National Institute for Health Research, and Wellcome Trust.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
147
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(151 citation statements)
references
References 36 publications
4
147
0
Order By: Relevance
“…) . ABO was also excluded from this analysis, as accurate prediction of this phenotype often requires precise phasing algorithms …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…) . ABO was also excluded from this analysis, as accurate prediction of this phenotype often requires precise phasing algorithms …”
Section: Resultsmentioning
confidence: 99%
“…Analysis of structural variations from the 1000 Genomes Project has been published, but its precision is limited . Homologous genes also pose the risk of misalignment of the short NGS reads produced by this project, and their accurate immunohematology interpretation may require locus‐specific adjustment of filter thresholds, as illustrated by recent publications . Thus, in the absence of experimental validation data and targeted filter adjustment, structural variants greater than 50 bp and homologous blood group genes with known recombination events ( RHD, RHCE, GYPA, GYPB, and GYPE ) were deferred from this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proof of principle study by Lane et al () showed that these challenges can be managed. The next step was to improve and automate the data analysis for blood group profiling as described in the next two sections (Moller et al , ; Lane et al , ).…”
Section: Complete Blood Group Profiles From Wgs Datamentioning
confidence: 99%
“…A small number of complex RH hybrids were correctly defined by the refined algorithm although there is still a need for validation on more complex samples, including samples from diverse ethnic backgrounds (Lane et al , ; Flower et al , ).…”
Section: Automated Typing Algorithms For Blood Group Profilingmentioning
confidence: 99%